p38γ and p38δ Are Involved in T Lymphocyte Development - Risco, Ana; Martin-Serrano, Miguel A.; Barber, Domingo F.; Cuenda, Ana (Frontiers in Immunology, 2018)
p38MAP kinase (MAPK) signal transduction pathways are essential regulators of the immune response. Particularly, p38γ and p38δ regulate many immune cell functions such as cytokine production, migration or T cell activation; however, their involvement in immune cell development is largely unknown. Here we analysed the role of p38 MAPK isoforms p38γ and p38δ in T cell differentiation in the thymus and in lymph nodes, using mice deficient in p38γ, p38δ, or in both. We found that the T cell differentiation program in the thymus was affected at different stages in p38γ-, p38δ- and p38γ/δ-deficient mice, and also peripheral T cell homeostasis was compromised. Particularly, p38δ deletion affects different stages of early CD4-CD8- double negative thymocyte development whereas lack of p38γ favours thymocyte positive selection from CD4+CD8+ double positive to CD4+ or CD8+ single positive cells. Our results identify unreported functions for p38γ and p38δ in T cells.